Investigation the effect of angle of placement in multilayer composite fibers on the performance of steel shear walls under nonlinear static analysis - Ashkan Khodabandehlou; Maryam Minadi (مدل‌سازی پیشرفته در مهندسی عمران, 2024)
The selection of the lateral system is done by considering the architectural constraints, load combination, gravity load transferring, structural dimension, codes constraints and etc. In this regard, in the last two decades, the use of steel shear wall system in new structures and reinforcement of existing buildings for greater resistance to lateral forces due to the seismicity of Iran is increasing. The main advantages of these systems are high elastic stiffness, high ductility, stable hysteresis behavior in reciprocating loading, as well as easier construction and installation and ease of opening. Since buckling occurs in the steel plate used as a wall, it is very common to use reinforced polymer carbon fiber (CFRP) with special properties such as high stiffness and strength, to reduce this buckling and also increase the energy absorption capacity. And wasting it can be very effective. Web steel plate in steel shear walls can be reinforced with carbon layers on both sides. In this type of composite steel shear wall, such as unreinforced steel shear wall, the web plate has low buckling strength and the shear capacity of the system is borne by diagonal tension fields in the composite sheet. In this particular type of steel shear wall, the role of reinforced polymer fibers in increasing the shear strength after buckling and the secondary stiffness of the system is significant. This system has both positive properties of unreinforced steel shear wall such as low cost and high execution speed and also has positive features of reinforced steel shear wall such as high stiffness and strength in displacement control. For static analysis of a composite structure made of different layers, due to the fact that the properties of fiber-reinforced composites are different in different directions, a number of parameters must be considered to obtain the optimal stress and deflection of the structure. Among these parameters, we can mention the addition of reinforcers, the effect of different orientations of the fibers, the effect of the number and thickness of layers, and the study of different fibers. In this research, by applying changes in positioning angle and number of fibers to achieve the best seismic performance, sixteen models have been geometrically and nonlinearly analyzed using ABAQUS finite element software. In modeling, wide wing profile number 20 as beam and column elements, steel sheet with thicknesses of 0.8, 1 and 1.5 mm and dimensions of 1.6 * 3.8 m for different samples as wall filling sheet has been used. The dimensions of the panel bays in all models are 4 meters and the height of the panels is 2 meters. In all models, the connection of the beam to the column is rigid and the connection of the sheet to the beam and column is hinged. The results of the research show that the best angles for the orientation of the layers are 45% and 60%. In addition, the use of carbon fiber improves seismic performance and increases parameters such as strength, ductility, equivalent plastic strain, depreciation and energy absorption by approximately 40%, which can be a desirable advantage for a lateral system be considered.